2017
DOI: 10.3390/v9010005
|View full text |Cite
|
Sign up to set email alerts
|

Mx Is Not Responsible for the Antiviral Activity of Interferon-α against Japanese Encephalitis Virus

Abstract: Mx proteins are interferon (IFN)-induced dynamin-like GTPases that are present in all vertebrates and inhibit the replication of myriad viruses. However, the role Mx proteins play in IFN-mediated suppression of Japanese encephalitis virus (JEV) infection is unknown. In this study, we set out to investigate the effects of Mx1 and Mx2 expression on the interferon-α (IFNα) restriction of JEV replication. To evaluate whether the inhibitory activity of IFNα on JEV is dependent on Mx1 or Mx2, we knocked down Mx1 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…BFA has also been reported to have antiviral activities against some viruses including poliovirus [ 14 ] and Rotavirus [ 15 ]. Recently, Zhou et al demonstrated the inhibitory effect of BFA on Japanese encephalitis virus (JEV) in BHK-21 cells [ 16 ]. To our knowledge, this is the first report to demonstrate antiviral activity of BFA on DENV.…”
Section: Resultsmentioning
confidence: 99%
“…BFA has also been reported to have antiviral activities against some viruses including poliovirus [ 14 ] and Rotavirus [ 15 ]. Recently, Zhou et al demonstrated the inhibitory effect of BFA on Japanese encephalitis virus (JEV) in BHK-21 cells [ 16 ]. To our knowledge, this is the first report to demonstrate antiviral activity of BFA on DENV.…”
Section: Resultsmentioning
confidence: 99%
“…Semliki Forest virus and type C footand-mouth disease virus enter BHK-21 cells by clathrin-dependent endocytosis (16,17). Persistent JEV infection has been demonstrated in BHK-21 cells, and numerous studies on JEV have been conducted in BHK-21 cells (18)(19)(20)(21); however, the precise entry mechanism for JEV internalization into BHK-21 cells remains unclear.…”
mentioning
confidence: 99%
“…Furthermore, recent studies have shown that poMx1 inhibits the replication of foot-and-mouth disease virus (FMDV) and bovine viral diarrhea virus (BVDV) (27,28). However, our research has shown that neither poMx1 nor poMx2 is responsible for the antiviral activity of IFN-␣ against Japanese encephalitis virus (JEV) (29). Our work has shown that wild-type (WT) poMx1 inhibits CSFV replication although the molecular mechanism of the inhibition remains to be elucidated.…”
mentioning
confidence: 76%
“…Plasmid construction and cell transfection. pcDNA3.0-poMx1-HA, pcDNA3.0-poMx2-HA, pEGFP-poMx1, and pEGFP-poMx2 have been described previously (26,29). The human MxA gene (UniProt ID P20591) and mouse Mx1 gene (UniProt ID P09922), which were kindly provided by Song Gao (Sun Yat-sen University Cancer Center, Guangzhou, China), were cloned into pcDNA3.0 fused to an HA tag or pEGFP-C1, creating pcDNA3.0-huMxA-HA, pcDNA3.0-mmMx1-HA, pEGFP-huMxA, or pEGFP-mmMx1.…”
Section: Methodsmentioning
confidence: 99%